Influence of organo-mineral supplementation on the production of secondary metabolites in in vitro-germinated Bromelia balansae Mez. (Research, Society and Development, 2021)
This work details the investigation of the influence of organo-mineral supplementation on the production of secondary metabolites in in vitro-germinated Bromelia balansae Mez. The seeds were germinated in vitro and transplanted to standard soils to undergo organo-mineral supplementation. The fully-grown plants were subjected to qualitative phytopharmacological prospection; quantitative analysis of total phenols and flavonoids; as well as chemical profiling by mass spectrometry. The in vitro germination of B. balansae was successful, with a germination rate of 94.95 %, thereby equaling to “super seeds” reported in literature. Moreover, the organo-mineral supplementation enhances the production of secondary metabolites in both leaves and roots, what therefore leads to higher yield of total phenols and flavonoids. Furthermore, mass spectrometry analysis confirmed the results from phytopharmacological prospection, and allowed the detection of fragments of secondary metabolites from shikimate/polyketide/mevalonate pathways.